Focal Length Lens Effect at Non-Metric Camera for Three-Dimensional Models Result - Nur Alfan Wisnu Hardiatmojo; Martinus Edwin Tjahjadi; Fransisca Dwi Agustina (Politeknik Negeri Batam, 2022)
Selections of non-metric cameras can be calculated properly starting from choosing the right camera sensor size and lens focal length to get better results. Differences in the choice of focal length in shooting can affect the resulting photo. The resulting photo may differ from how much of the object is captured and may suffer distortion due to different selections of the focal length. The purpose of this study is to show the magnitude of the effect of focal length variation in making a three-dimensional model based on the comparison of the results of the three-dimensional model visualization, the comparison of the results of geometric accuracy based on the independent checkpoint coordinate data, and the comparison of the distance results between retro targets. The results of this study indicate that a focal length of 70 mm has better results with the formation of the object completely resembling its original object compared to a focal length of 28 mm which is not good at forming a safety pillar on the bridge. The results of the RMSE value based on ICP coordinate data at a focal length of 70 mm are better with a value of 0.083 m compared to a focal length of 28 mm with a large value of 0.123 m. The results of the RMSE value based on the distance between retro targets at a focal length of 70 mm are better with a value of 0.003 m compared to a focal length of 28 mm with a large value of 0.004 m.